2005
DOI: 10.1111/j.1523-1755.2005.67132.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-dominant polycystic kidney disease as a risk factor for diabetes mellitus following renal transplantation

Abstract: In our study patients with ADPKD were at a threefold increased risk for development of posttransplant diabetes mellitus within the first year following renal transplantation. Development of posttransplant diabetes mellitus was associated with a significant detrimental impact on patient survival. Further studies are needed to provide insight into the mechanisms of the association between ADPKD and posttransplant diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 20 publications
1
36
1
2
Order By: Relevance
“…[14][15][16] Whether this association is due to an increased risk of maturity-onset diabetes of Table 2. Relationship between TCF7L2/HNF1β genotypes and NODAT RESEARCH the young (MODY) type 5 (also known as 'renal cyst and diabetes' syndrome) in this group of patients is worth exploring.…”
Section: Researchmentioning
confidence: 99%
“…[14][15][16] Whether this association is due to an increased risk of maturity-onset diabetes of Table 2. Relationship between TCF7L2/HNF1β genotypes and NODAT RESEARCH the young (MODY) type 5 (also known as 'renal cyst and diabetes' syndrome) in this group of patients is worth exploring.…”
Section: Researchmentioning
confidence: 99%
“…Beyond hypertension, other metabolic abnormalities have also been reported to occur more frequently in ADPKD patients relative to a healthy control population, resulting in coronary artery disease [22]. Several articles have reported that ADPKD patients exhibit an increased incidence of post-transplant diabetes mellitus or new-onset diabetes after transplantation [23-25], indicating that an increased diabetogenic state arises due to ADPKD itself. HLA-B27 has been reported to be a potential risk factor for post-transplant diabetes mellitus in those with ADPKD [26].…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant or recessive polycystic kidney disease is also linked to NODAT (ref. [16][17] ). A plausible mechanism for the association needs to be explained.…”
Section: Genetic Backroundmentioning
confidence: 99%